The measurement of thrombin in clotting blood by radioimmunoassay. - Shuman, M A (1976)
We have developed a radioimmunoassay for human thrombin using rabbit anti-human thrombin IgG. The assay can measure 2 ng thrombin/ml plasma, 500-fold more sensitive than clotting assays. Human prothrombin is less reactive in the assay than thrombin by at least four orders of magnitude, and there is no demonstrable cross-reactivity with human factor Xa, the clotting factor structurally most similar to thrombin. The assay does not detect thrombin bound to anthithrombin III. Using the assay, we have demonstrated that plasma from 20 normal subjects does not contain detectable thrombin. We measured thrombin generation in clotting blood in polypropylene tubes and observed that thrombin appears (approximately equal to 3 ng/ml) within 45 S-5 min after venipuncture. This material is thrombin, not intermediates of prothrombin activation, since it disappears after addition of heparin, which promotes thrombin antithrombin III complex formation. After a plateau of 2-10 min, there is further thrombin generation, which results in clotting after 15-27 min at a level of 40-50 ng thrombin/ml. The thrombin generated 9-25 min before clotting may activate factors V and VIII and stimulate platelet aggregation and release. In contrast, the cascade hypothesis assigns a role for thrombin only late in blood clotting. Radioimmunoassay of thrombin and other clotting factors will be useful for clinical and physiological studies of blood clotting especially since the assay seems specific for thrombin and is independent of other activities that affect bioassays.